Movement Analysis of Fundamental Forehand and Backhand Tennis Techniques for Athletes at the Sekadau Regency PELTI Introductory Tennis Club - Ilham Perani; Ade Rahmat; Suriani Sari (Inspiree)
The  purpose  of  the study. The objective of this study is to assess the fundamental forehand and backhand tennis movement competencies for beginner PLTI tennis players in the Sekadau district.